Electrochemical Performance of Lithium Titanate Submicron Rods Synthesized by Sol‐Gel/Electrospinning. Issue 11 (2nd September 2014) - Haridas, Anulekha K.; Sharma, Chandra S.; Rao, Tata N.; Aggarwal, Suresh K.
Abstract Lithium titanate (LTO) submicron rods with grain sizes varying from 50–80 nm were synthesized without any polymer additive by sol‐gel assisted electrospinning. The obtained phase pure (spinal phase) LTO submicron structures exhibited fast charge/discharge profiles at varying charging rates (C rates). After initial charge/discharge studies at various C rates (0.1 C – 30 C) followed by at 1 C rate for 200 cycles, the cell has shown specific capacity of 140.6 mA h/g with columbic efficiency of 99.8 %. The ordered crystalline nanostructure enabling reduced diffusion path could explain this excellent performance of LTO submicron rods which may find potential applications as anode materials in lithium ion battery for electric vehicles.